A history of securities law in the Supreme Court - Pritchard, Adam C.; Thompson, Robert B. (Law Professor) (New York, NY : Oxford University Press, 2023)
This comprehensive history of modern US securities law illustrates the key jurisprudential changes at the Supreme Court since the New Deal. The authors use the justices' internal memos, notes, and preliminary drafts to tell the story of how they actually decided the cases. The securities laws were an ambitious expansion of the administrative state. That expansion required a transformation of the Court's approach to business regulation, abandoning the Court's prior hostility to government intervention.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 24, 2023).
Keywords: Securities -- United States; United States. -- Supreme Court; Law; Laws of specific jurisdictions & specific areas of law